Qualidade na gestão do planejamento: ato administrativo digital e eficiência na regulação municipal - Richardo, Rodolfo Luiz Maderic (2013)
The exemptions for Public Administration are enhanced by greater attendance trends aimed at the Principle of Efficiency , sure the Planning Management should rely on administrative acts digital and greatly enhance the state action . There is need , however, that such practices , not as a mark of excessive bureaucracy , are regulated under the terms and limits of the Principles of Legality and the Supremacy of the Public Interest . The activities of the state are expanded in essential services and interventions in Economics , and the municipalities , this approach symmetric and regional can and should emerge as federal units decentralized and efficient in Public Management . While the managerial and bureaucratic model is still unfeasible in dealing with the regulation of state affairs arises therefore the possibility of Planning seeking qualitative methods electronics.